DIETARY ANALYSIS OF REGIONAL AND NATIONAL LEVEL YOUTH SWIMMERS IN THE UNITED KINGDOM. Issue 17 (24th October 2013) - Russell, M; Lali, R; Cockburn, E; Rumbold, PLS
Abstract : Optimised nutritional intake is well established as being one of a multiplicity of factors that contributes to the development of attaining peak sporting performance. Few studies have sought to investigate the dietary habits of adolescent, as opposed to adult, swimmers; especially those competing in the United Kingdom. Therefore the purpose of this study was to investigate the nutritional and activity habits of amateur swimmers (n=25; Age: 15±1 years; Stature: 1.67±0.02 m; Mass: 56.2±1.7 kg; BMI: 20.1±0.4 kg·m 2 ) who trained and competed on behalf of Regional and National Development Squads based in the UK. All participants recorded their 4 day dietary intake and activity habits during a typical week that included ∼9 h of training (consisting of 1 h land training with the remaining time dedicated to swim training with a speed emphasis). The intake of carbohydrates (6.2±0.4 g·kg −1 ·d −1 ), proteins (1.8±0.1 g·kg −1 ·d −1 ) and fats (1.9±0.1 g·kg −1 ·d −1 ) represented 52±1%, 15±1%, and 36±1% of the mean daily energy intake, respectively. Compared to Recommended Nutrient Intake values, micronutrient deficiencies were observed for fibre (45±4% of RNI), vitamin A (52±7% of RNI) and selenium (72±6% of RNI), whereas all other analysed micronutrients met or exceeded recommendations. A mean daily energy deficit of 956±135 KCal existed. These data suggest that the nutritional practices of a group of amateur swimmers were less than optimal when seeking to sustain peak performance throughout training. Consequently, based on current dietary recommendations, if complete recovery, delay of fatigue and a reduced susceptibility to illness is desired, adolescent swimmers should seek to ensure that their dietary intake contains an optimised proportion of energy derived from macronutrients while ensuring that enough foods containing fibre, vitamin A and selenium are consumed.